Microbial Electrosynthesis Using 3D Bioprinting of Sporomusa ovata on Copper, Stainless-Steel, and Titanium Cathodes for CO2 Reduction - Bajracharya, Suman; Krige, Adolf; Matsakas, Leonidas; Rova, Ulrika; Christakopoulos, Paul (Fermentation (Basel), 2024)
Acetate can be produced from carbon dioxide (CO2) and electricity using bacteria at the cathode of microbial electrosynthesis (MES). This process relies on electrolytically-produced hydrogen (H2). However, the low solubility of H2 can limit the process. Using metal cathodes to generate H2 at a high rate can improve MES. Immobilizing bacteria on the metal cathode can further proliferate the H2 availability to the bacteria. In this study, we investigated the performances of 3D bioprinting of Sporomusa ovata on three metal meshes—copper (Cu), stainless steel (SS), and titanium (Ti), when used individually as a cathode in MES. Bacterial cells were immobilized on the metal using a 3D bioprinter with alginate hydrogel ink. The bioprinted Ti mesh exhibited higher acetate production (53 ± 19 g/m2/d) at −0.8 V vs. Ag/AgCl as compared to other metal cathodes. More than 9 g/L of acetate was achieved with bioprinted Ti, and the least amount was obtained with bioprinted Cu. Although all three metals are known for catalyzing H2 evolution, the lower biocompatibility and chemical stability of Cu hampered its performance. Stable and biocompatible Ti supported the bioprinted S. ovata effectively. Bioprinting of synthetic biofilm on H2-evolving metal cathodes can provide high-performing and robust biocathodes for further application of MES.